Serotonin receptors and their ligands - Olivier, Berend; Wijngaarden, I. van; Soudijn, W. (Pharmacochemistry library ;, 1997)
An international group of authors have produced an overview of the progress made in the medicinal chemistry of compounds (selectively) acting at serotonin receptors or serotonin transporters either as agonists, partial agonists or antagonists. Structure - affinity relationships and structure - activity relationships of agonists, partial agonists, and antagonists of 5-HT receptors and uptake sites, are discussed. Structure, sequence homology and the effect of site-directed mutations of 5-HT receptors and the reuptake site on the binding of ligands show the tremendous impact of molecular biology on medicinal chemistry research. Also discussed is the pharmacology and (potential) clinical applications of ligands for the 5-HT receptors and the reuptake site. By developing elegant techniques of cloning and expression of serotonin receptor subtypes, their mutants and chimeras, a unique opportunity was offered to study the binding mode of serotoninergic ligands to their receptors and transporters. The distribution, structure and homologies of serotonin receptor subtypes and the structure of the serotonin transporter are also taken into account. The (potential) therapeutic applications of ligands of the different subtypes are described. Altogether an excellent addition to the Pharmacochemical Library series.